DREDGERS: TECHNOLOGIES FOR REMOVING UNDERWATER SEDIMENTS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
A dredger is a type of pump that removes a water-slurry mixture from a central intake. It differs from ordinary water pumps in that it has a more robust casing and fewer paddles on the impeller. The pump usually has 3-6 paddles, which allow sediments and other materials (such as small stones, metal, glass, and various plant roots) to pass through. If these materials get clogged inside the pump, an opening is made in the pump casing for cleaning, and it is then sealed with a special cover and bolted shut. A floating machine equipped with dredging equipment is called a "dredger" (zemsnaryad). It is used to suction underwater sediments (softening hard sediments if necessary) along with water and transport them. The overall design of the dredger includes a diesel-electric engine, a dredge, a winch, a pile driver, and other related equipment. The electrical energy produced by a generator connected to the power unit (IYOD) is supplied to the dredger, the dredge, and the electric motors that power the sediment softening and winching systems. This article provides a detailed analysis of the operating principles, structure, and technical specifications of dredgers and dredge pumps.